A COMPARATIVE ANALYSIS OF INFORMED CONSENT LEGISLATION IN UKRAINIAN AND LATVIAN LEGISLATION AND CASE LAW - Henryk Malewski; Egidijus Vidmantas Kurapka; Snieguolė Matulienė; Valery Shepitko; Mykhaylo Shepitko; Rafał Cieśla (International Comparative Jurisprudence, 2022)
The paper is dedicated to the comparative research of the views of the students representing the universities of three countries in terms of usefulness (necessity) of studying the criminalistic disciplines for future legal professionals. The core of this research is a coordinated and unified questionnaire study of 758 students from three Universities in Lithuania (Mykolas Romeris University), Ukraine (Yaroslav Mudryi National Law University) and Poland (University of Wroclaw). Modern pedagogics considers students to be not only future professionals, but likewise active participants in improving the didactic process. In recent decades, criminalistics has become increasingly important. This paper is a fragment of a broader study that is aimed not only at investigating the current situation in the criminalistic didactics of these countries in the run-up to the creation of a single European criminalistic space, but it is likewise aimed at future professionals, educators and managers of educational institutions, who are to implement this idea. The paper is not only a presentation of law students’ views on expediency and necessity of studying criminalistics and other disciplines of criminalistic orientation important for their future professional activities, but it should likewise become a kind of guide to action for teachers and administration of universities, i.e. to improve substantive and organizational as well as methodological aspects of criminalistic didactics. The given technique of research of students’ views can be successfully applied when addressing the problems of teaching other disciplines.